INNOVATIVE MARKETING IN MARKETING MANAGEMENT SYSTEM OF ENTERPRISES: REASONS AND KEY VECTORS OF DEVELOPMENT - LARINA, Yaroslava; GALCHYNSKA, Julia; DICHENKO, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers the issues of terminology, essence and meaning of the concept of "innovative marketing" from the historical and practical points of view, characterizes the main vectors of development and trends in Ukraine. The purpose of the article is to clarify the content and identify the characteristic features of innovative marketing in the marketing management system of enterprises at the current stage, structuring the elements of innovative marketing of the enterprise. Innovative marketing is considered in the article as a component of marketing management which involves the analysis of market changes and demand for goods and services, the study of directions for effective changes (optimization), introduction to the market and sale of products on this basis. At the same time, marketing management, including strategic planning must necessarily include the development of new goods (services) and the strategy of optimizing the product portfolio depending on market changes (based on the analysis of tendencies and trends). The article proves that Innovative marketing covers all areas of marketing activity in aggregate, marketing mixes that are relevant in current conditions and include modern innovative means and tools, including digital marketing. As for "marketing innovations", they are defined as the introduction of new marketing practices involving significant changes in the design, distribution, promotion or pricing of a product or service. Thus, innovative marketing and marketing innovation are correlated as a whole and a part. The relevance of using innovative marketing in various types of business activity is constantly growing, especially in high-tech industries and the service sector. Innovative marketing includes such key elements as the creation and promotion of an innovative product, innovative service, and innovative technologies. In turn, marketing innovations include place, product, price, promotion and their mix. The proposed classification of marketing innovations covers possible options for the application of innovations by elements of the marketing complex and auxiliary marketing activities, including: the use of the latest marketing research methods based on digital marketing tools; choosing one of the modern marketing concepts with an emphasis on advantages in ecology, social responsibility or building sustainable relationships; choosing a marketing strategy to cover the market and expand the target audience; product positioning and repositioning; changes in the assortment policy of an innovative nature; improvement of sales policy; modification (optimization for the enterprise) of the product life cycle; optimization of pricing policy with the use of innovative approaches in pricing; application of innovative methods of product promotion based on digitization. Conclusions are drawn on the main parameters of the effective use of innovative marketing.
Keywords: marketing; innovations; innovative marketing; marketing management; enterprise; digitalization; development